Relationship between resting heart rate, symptoms and exacerbation in patients with chronic obstructive pulmonary disease (COPD) / Aisya Natasya Musa - Musa, Aisya Natasya (2015)
Introduction: Resting heart rate is a readily available data and has been shown to be associated with mortality in COPD patients. However, there is a lack of data on whether it has any association with exacerbation, symptoms and spirometric parameters in COPD patients. This study aims to identify the association between resting heart rate and exacerbation, symptoms and spirometric parameters. Methodology: This is a multi-centre cohort study with 12 months follow up of COPD patients recruited during acute exacerbation of COPD requiring hospitalisation from 1st April 2012 till 30th September 2015. Patient's sociodemographic data, anthropometric indices and medications history were recorded at recruitment. Subjects were then followed up in clinic at 3 months after the recruitment (Month 0) and Month 6 and Month 12 where baseline resting heart rate was taken (Month 0), spirometry was done, and CAT score completed. In between, there were 2 telephone interview follow up where exacerbation history was asked (Month 3 and 9). Results: A total of 147 patients were recruited in this study. The mean age of our patients was 66.76 ± 9.25 year. 76.9% of patients had higher resting heart rate (> 80 bpm). The mean resting heart rate was 86.91 ± 13.01 bpm. The higher resting heart rate patients had a significantly higher proportion of exacerbators compared to the lower resting heart rate group at month 3 (54.4% vs. 26.9%, p=0.013). The trend was followed through until month 9. There were also statistically significant moderate strength linear correlation between resting heart rate and exacerbation frequency per epoch at month 3, month 6 and month 9 (r = 0.400, p < 0.001; r = 0.440, p < 0.001; and r = 0.416, p = 0.004). The mean exacerbation frequency (per epoch) was also significantly higher in the higher resting heart rate group at month 3 and month 6 (2.00 vs. 0.48, p<0.001; and 3.42 vs. 1.14, p = 0.004). There was a significant positive correlation between resting heart rate and CAT score at month 6 (r = 0.312, p = 0.011). However, this study did not identify any relationship between resting heart rate and FEVi percentage predicted. Conclusion: COPD patients with higher resting heart rate following exacerbation requiring hospitalisation demonstrated increased risk of exacerbation, with higher exacerbation frequency seen at 3, 6 and 9 months of follow up. There was also an association with symptoms assessed by CAT score at 6 months.